The identity and role of the radiologist in 2020: a survey among ESR full radiologist members - European Society of Radiology (ESR) (Insights into Imaging, 2020)
Abstract Background Radiologists undertake a wide variety of functions which have altered as technologies have evolved. The aim of this survey was to explore radiologists’ opinions concerning their role and identity in 2020. Methods The survey included 124 questions on training, daily work, interaction with colleagues and patients, involvement in teaching, research and management and task delegation. An initial draft was amended following responses from the Presidents of the 48 ESR’s national institutional member societies. The final on-line survey was available to individual ESR full members between January and March 2020. 1344 responses from radiologists in 49 European countries were obtained. Findings 80% (1049/1317) of radiologists considered a period of non-radiology clinical training mandatory and 92% (1192/1291) felt that sub-specialty expertise was important and improved the visibility of radiologists. 76% (961/1262) of radiologists regularly communicate directly with patients. Only 25% (314/1238) had undergone formal communications training although 82% (1020/1238) felt that this would be beneficial. Radiologists highly value their positive interaction with colleagues, including within multi-disciplinary team meetings, despite limited resources. Difficulties identified included high workload, especially the need to cover general work in parallel with the need to offer subspecialty expertise. 66% (837/1262) felt that lack of visibility to patients is a risk to radiology and professional visibility could be improved by radiology-led research and teaching. Conclusions ESR activities should aim to (1) support radiologists with sub-specialty training and maintenance of competencies; (2) develop recommendations for patient communications training and multi-disciplinary working with strong clinical integration; (3) enhance radiologists’ visibility by harnessing opportunities for radiology-led research and education.